Adverse childhood experiences, developmental differences in impulse control and sensation seeking, and delinquency: A prospective multi-cohort study. (September 2022) - Meldrum, Ryan C.; Stults, Brian J.; Hay, Carter; Kernsmith, Poco D.; Smith-Darden, Joanne P.
Abstract: Purpose: Developmental trajectories of low impulse control coupled with high sensation seeking are associated with greater adolescent delinquency. In addition, several studies link adverse childhood experiences (ACEs) to lower self-control and increases in delinquency. Herein, we develop and test an integrated model which synthesizes these two strands of research. Methods: Using four waves of panel data from the Supporting Healthy Adolescent Relationships and Environments (SHARE) study, we estimate latent classes representing dual trajectories of impulse control and sensation seeking to investigate if the association between ACEs and delinquency operates indirectly via class membership among two cohorts of youth. Results: Greater exposure to ACEs is associated with membership in latent classes characterized by greater sensation seeking and lower impulse control. In addition, membership in such classes is positively associated with delinquency, and the association between ACEs and delinquency is partially mediated by class membership in each cohort of youth. Conclusions: Findings demonstrate the utility of integrating insights from multiple fields to study the cascading effects of ACEs. Still, there appear to be additional avenues through which ACEs shape later involvement in delinquency that extend beyond the dual systems framework, necessitating additional research on other potentially relevant mechanisms. Highlights: ACEs are associated with latent classes of impulse control and sensation seeking. Latent class membership is associated with involvement in delinquency. Latent class membership partially mediates the ACEs-delinquency association. These patterns were observed in two separate cohorts of youth.